2010
DOI: 10.1007/s10592-009-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Founding population size of an aquatic invasive species

Abstract: Non-native species of fish threaten native fishes throughout North America, and in the Rocky Mountains, introduced populations of lake trout threaten native populations of bull trout. Effective management of lake trout and other exotic species require understanding the dynamics of invasion in order to either suppress non-native populations or to prevent their spread. In this study, we used microsatellite genetic data to estimate the number of lake trout that invaded a population of bull trout in Swan Lake, MT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…Instead, we added STRUCTURE (Pritchard et al. 2000), one of the most commonly used aspatial Bayesian clustering methods (Kalinowski et al. 2010), and one often employed as a benchmark for method comparison (e.g., Jombart et al.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, we added STRUCTURE (Pritchard et al. 2000), one of the most commonly used aspatial Bayesian clustering methods (Kalinowski et al. 2010), and one often employed as a benchmark for method comparison (e.g., Jombart et al.…”
Section: Methodsmentioning
confidence: 99%
“…The application of molecular approaches to introduced populations can reveal hybridization and introgression (Holsbeek et al 2008, Parham et al 2013, Gering et al 2015, elucidate geographic origin (Jousson et al 2000, Johnson et al 2011, Siler et al 2014), infer population demography (Thibault et al 2009, Kalinowski et al 2010Purcell et al 2012), and elucidate the presence of cryptic species (May and Marsden 1992, Holland et al 2004, Stepien and Tumeo 2006. Genetic approaches are particularly helpful when unraveling introduction events that involve taxonomically problematic, sympatric and morphologically indistinguishable species, a situation particularly common to aquatic introductions (see Booth et al 2007 andGeller et al 2010 for recent reviews).…”
Section: Introductionmentioning
confidence: 99%
“…In some species, inbreeding depression has been shown to lower the potential to deal with stressful conditions (e.g., Armbruster et al, 2000;Larson et al, 2009) and to lead to an increased liability of population extinction (Saccheri et al, 1998;Bijlsma et al, 2000;Wright et al, 2008). In a number of studies, however, no negative effects of inbreeding were reported after recovery from severe population bottlenecks (e.g., Ellegren et al, 1993;Hoelzel et al, 1993Hoelzel et al, , 2002Groombridge et al, 2009), and in some cases invasive species have been shown to thrive despite going through strong bottlenecks (e.g., Hawley et al, 2008;Kalinowski et al, 2010;SchmidHempel et al, 2007). This suggests that there are mechanisms that decrease the fitness costs of inbreeding.…”
Section: Introductionmentioning
confidence: 99%